Pengembangan E-modul Bioteknologi Berbasis Flipbook Interaktif di Jurusan Biologi Universitas Negeri Medan - Putriana Purba; Diky Setya Diningrat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The rapid development of digital technology has made a significant contribution to education, especially in improving the quality of the learning process. The study aims to develop and test the feasibility, student response, and effectiveness of using interactive Flipbook-based Biotechnology E-modules on Fermentation Technology material. The research was conducted in April-July 2025 at Medan State University using the ADDIE development model. The research instrument was an assessment questionnaire involving material experts, media experts, question experts, and students. The validation results showed that the developed E-module was rated very feasible by media experts (92.5%), feasible by material experts (78.5%), and very feasible by question experts (95.4%). The response of Biology Education Study Program students at Medan State University to the E-module was in the very good category with a percentage of 90%. The effectiveness test showed that the E-module developed had a high level of effectiveness with an N-Gain value of 0.71. These results indicate that the Biotechnology E-module on Fermentation Technology material is feasible to use as a learning media to improve student learning outcomes.